2009
DOI: 10.1088/1475-7516/2009/11/028
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic trispectrum of curvature perturbations induced by primordial non-Abelian vector fields

Abstract: Motivated by the interest in models of the early universe where statistical isotropy is broken and can be revealed in cosmological observations, we consider an SU (2) theory of gauge interactions in a single scalar field inflationary scenario. We calculate the trispectrum of curvature perturbations, as a natural follow up to a previous paper of ours, where we studied the bispectrum in the same kind of models. The choice of a non-Abelian set-up turns out to be very convenient: on one hand, gauge boson self-inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 95 publications
0
31
0
Order By: Relevance
“…In fact, the two results (41) and (51) have been first obtained in [39] for I ∝ a 2 . Although the mechanism (2) was first introduced with this motivation, the magnetogenesis application suffers a strong coupling problem [26].…”
Section: Magnetogenesismentioning
confidence: 82%
See 1 more Smart Citation
“…In fact, the two results (41) and (51) have been first obtained in [39] for I ∝ a 2 . Although the mechanism (2) was first introduced with this motivation, the magnetogenesis application suffers a strong coupling problem [26].…”
Section: Magnetogenesismentioning
confidence: 82%
“…In Section III we study how these modes δA are coupled to the modes of ζ through (2). The power spectrum and bispectrum of ζ are computed respectively in Sections IV and V. There, we show explicitly how the sum of the long-wavelength modes adds up with the solution of the classical equations of motion to determine the 3 For previous works on anisotropic non-gaussianity, see [28][29][30][31][32][49][50][51][52][53][54][55].…”
mentioning
confidence: 99%
“…On the other hand, a connected anisotropic contribution to the curvature trispectrum is expected to create some non-vanishing off-diagonal signals, as well as diagonal ones due to τ NL . It is known that anisotropic trispectrum signals can also be produced in vector inflation models [40][41][42][43][44], while there may exist other possible models where unknown anisotropic signals are realized. The trispectrum parametrization is still nontrivial and the resultant µ-µ signatures need to be analyzed on a case-by-case basis.…”
Section: µ-T Correlation Due To Primordial Anisotropic Non-gaussmentioning
confidence: 99%
“…The initial interests in inflaton-gauge interactions rooted from the quest to generating anomalous features during inflation, e.g. statistical anisotropy of CMBR [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], primordial gravitational waves that potentially break the Lyth bound [31,32], large scale seed magnetic fields [33][34][35], and primordial non-Gaussianity [31,[36][37][38][39][40][41][42][43]. Eventually, it has been found that the back reaction of the generated gauge fields slows down the inflaton and alleviates the necessity of flat potential [44][45][46].…”
Section: Introductionmentioning
confidence: 99%